Three-dimensional models of core-collapse supernovae from low-mass progenitors with implications for Crab. Issue 2 (15th June 2020) - Stockinger, G; Janka, H-T; Kresse, D; Melson, T; Ertl, T; Gabler, M; Gessner, A; Wongwathanarat, A; Tolstov, A; Leung, S-C; Nomoto, K; Heger, A
ABSTRACT: We present 3D full-sphere supernova simulations of non-rotating low-mass (∼9 M⊙ ) progenitors, covering the entire evolution from core collapse through bounce and shock revival, through shock breakout from the stellar surface, until fallback is completed several days later. We obtain low-energy explosions (∼0.5–1.0 × 10 50 erg) of iron-core progenitors at the low-mass end of the core-collapse supernova (LMCCSN) domain and compare to a super-AGB (sAGB) progenitor with an oxygen–neon–magnesium core that collapses and explodes as electron-capture supernova (ECSN). The onset of the explosion in the LMCCSN models is modelled self-consistently using the vertex-prometheus code, whereas the ECSN explosion is modelled using parametric neutrino transport in the prometheus-HOTB code, choosing different explosion energies in the range of previous self-consistent models. The sAGB and LMCCSN progenitors that share structural similarities have almost spherical explosions with little metal mixing into the hydrogen envelope. A LMCCSN with less second dredge-up results in a highly asymmetric explosion. It shows efficient mixing and dramatic shock deceleration in the extended hydrogen envelope. Both properties allow fast nickel plumes to catch up with the shock, leading to extreme shock deformation and aspherical shock breakout. Fallback masses of 5 × 10^-3 M⊙ have no significant effects on the neutron star (NS) masses and kicks. The anisotropic fallback carries considerable angular momentum, however, and determines the spin of the newly born NS. The LMCCSN model with less second dredge-up results in a hydrodynamic and neutrino-induced NS kick of >40 km s −1 and a NS spin period of ∼30 ms, both not largely different from those of the Crab pulsar at birth.